The Concept of Economic Independence of Cash Waqf-Based Pesantren and Its Implementation at STIBA Ar Raayah - Husnul Khatimah; Nuradi; Nurul Huda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of the research is to find out how the concept of cash waqf model to achieve economic independence of pesantren and its implementation at STIBA Ar Raayah. This research uses a literature study with a qualitative approach. The results of this study highlight the importance of professional and trustworthy cash waqf investment management and the role of sustainable management in developing cash waqf models for education, especially in STIBA Ar Raayah Islamic boarding schools. The pesantren must be able to develop its capabilities by running a business independently to maintain its existence and no longer depend on its operational funding on students or donors. In terms of higher education pesantren, STIBA Ar Raayah Pesantren has a considerable potential for cash waqf of IDR 71,565,000 per month or IDR 858,780,000 per year or equivalent to USD 52,702 per year (assuming USD1 = IDR 16,269.06 as of June 05, 2024).